The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1515/pjvs-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical parameters in Japanese quails Coturnix coturnix japonica infected with coccidia and treated with Toltrazuril

Abstract: The activity of aspartate aminotransferase, alanine aminotransferase and lactate dehydrogenase, total protein, albumin and cholesterol levels were determined in the blood serum of Japanese quails infected with coccidia and treated with Baycox (active ingredient: toltrazuril). Lower levels of AST and ALT activity were noted in treated birds regardless of the applied Baycox dose. The biochemical changes observed in the blood serum of Japanese quails point to coccidia-induced damage of digestive system tissues de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
3
3
2
Order By: Relevance
“…Our average and minimal-maximal values of AST were similar to these obtained from Scholz et al (2009) in Japanese quails and from Gylstorff and Grimm (1998) in doves. Unlike cited studies and our results Nazifi and Asasi (2001), Hamidipour et al (2016), Sokół et al (2015), Panda et al (2017) and Abang et al (2017) found significantly lower values of AST in Japanese quails. Such lower values of AST were reported from Albokhadaim et al (2013) in local chickens from Saudi Arabia and Abou-Shehema et al (2016) in Bandarah chickens.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Our average and minimal-maximal values of AST were similar to these obtained from Scholz et al (2009) in Japanese quails and from Gylstorff and Grimm (1998) in doves. Unlike cited studies and our results Nazifi and Asasi (2001), Hamidipour et al (2016), Sokół et al (2015), Panda et al (2017) and Abang et al (2017) found significantly lower values of AST in Japanese quails. Such lower values of AST were reported from Albokhadaim et al (2013) in local chickens from Saudi Arabia and Abou-Shehema et al (2016) in Bandarah chickens.…”
Section: Discussioncontrasting
confidence: 95%
“…Regarding the data for the other liver enzyme ALT, it can be concluded that our results were higher than the reference range for Japanese quails, reported by Scholz et al, 2009. Similar results were found from Sokół et al (2015) in quails with experimental coccidiosis treated with toltrazuril. The values of ALT reported by Mnisi et al (2017) in 9 week old male Japanese quails, Hamidipour et al (2016) and Panda et al, (2017) in the same bird species were in line with our results.…”
Section: Discussioncontrasting
confidence: 49%
“…У навколишньому середовищі, а саме у ґрунті життєдіяльність ооцисти еймерій зберігають від шести місяців до двох років, а на територію господарства і в приміщення, де вирощується птиця, ооцисти заносяться на одязі та взутті обслуговуючого персоналу, інвентарем та ін. [15][16][17][18].…”
Section: вступunclassified
“…Отже, отримані дані підтверджують й інші автори, які встановили, що комбіновані схеми ліку-вання за наявності еймеріозу в перепелів більш ефективні порівняно з монотерапією, також відмічається нормалізація гематологічних показників [17][18][19]. Новизна наших науково-виробничих досліджень полягає в тому, що ми апробували, розробили дозування та період застосування настоянки лимонника китайського як імуностимулятора в перепільництві за наявності еймеріозу.…”
Section: біохімічні показники крові перепілок у разі лікування «брометронідом новим» у поєднанні з настоянкою лимонника китайського (M±m unclassified